KAJIAN TINGKAT PELAYANAN PENUMPANG DI BANDARA ADISUTJIPTO YOGYAKARTA - Mulyani, Sri; Hartini, Dwi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
Peak hours or peak hours and when there is an Air Force plane that doing regular exercise. Number apron at Yogyakarta Adisucipto international airport just 8 parking stand, while aircraft movement during peak hours reached 10 aircraft even more, so that the common line during the hours puncak. Untuk overcome this new airport Yogyakarta must be realized in order to fit with the capacity kebutuhannya.Kasus second, because the international airport Adisucipto a military-owned airports which are also used for commercial flights, then that becomes the top priority is owned aircraft Air Force. To Â and separate from military activities. So that flight activities more effective and can reduce the factor late arrival due to late landing. The technical problem is usually the plane will experience a delay can not predict how long the delay time and this factor also can not be in perediksi when it will be a problem with the engine, fuselage, landing gear, etc. So Line Maintenance personnel in the field should always be alert and responsive when things are going according to the maintenance manual. And always conduct appropriate inspection check list.